La réalité du comportement social scolaire des élèves du secondaire, Est de l’Algérie - hacini, amine; cherif, nacereddin (sports creativity, 2025)
The study aimed to find out the situation in the secondary schools of Algeria in the East through this study, as well as to identify the difference between males and females in school social behaviors and the degree of their practice among both sexes. The researcher followed the descriptive approach for the suitability of this curriculum for this study from the scientific side, and the research community consisted of several students from the secondary schools of Algeria in the east, and the sample was randomly drawn, as their number represented 100 students, 50 males and 50 females from different secondary schools, and the researcher used: the School Social Behavior Scale consisting of two measures, the Social Behavior Scale and the Anti-Social Behavior Scale. Among the most important findings are: Students of secondary schools in Algeria East have high behavioral skills